2015
DOI: 10.3390/rs70607995
|View full text |Cite|
|
Sign up to set email alerts
|

Estimating Leaf Bulk Density Distribution in a Tree Canopy Using Terrestrial LiDAR and a Straightforward Calibration Procedure

Abstract: Abstract:Leaf biomass distribution is a key factor for modeling energy and carbon fluxes in forest canopies and for assessing fire behavior. We propose a new method to estimate 3D leaf bulk density distribution, based on a calibration of indices derived from T-LiDAR. We applied the method to four contrasted plots in a mature Quercus pubescens forest. Leaf bulk densities were measured inside 0.7 m-diameter spheres, referred to as Calibration Volumes. Indices were derived from LiDAR point clouds and calibrated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…Visualization of the uncorrected 905 nm data as recorded by the scanner system did not allow clear dinstinction of vegetation characteristics. The same observation has been confirmed by Pimont et al (2015), where a detailed discussion of this phenomenon can be found. However, this motivated us to experiment with the automation of intensity correction methods directly from the field data.…”
Section: Datasupporting
confidence: 68%
“…Visualization of the uncorrected 905 nm data as recorded by the scanner system did not allow clear dinstinction of vegetation characteristics. The same observation has been confirmed by Pimont et al (2015), where a detailed discussion of this phenomenon can be found. However, this motivated us to experiment with the automation of intensity correction methods directly from the field data.…”
Section: Datasupporting
confidence: 68%
“…Various algorithms have been successfully developed to estimate tree height [26], leaf area index [27,28], aboveground biomass [29], canopy cover [7,30,31] at both individual tree [29,32,33] and forest stand scales [34,35]. However, studies on LiDAR-based CBH estimation are still insufficient, particularly at individual-tree scale.…”
Section: Introductionmentioning
confidence: 99%
“…The cases we explored here were intended as a simple first step, rather than a comprehensive evaluation; many aspects of fuel heterogeneity that can be represented in STANDFIRE and FuelManager were not used to their full effect in these examples. This capacity for finer detail should also enable use of more detailed fuel mapping approaches (Loudermilk et al 2012;Pimont et al 2015;Almeida et al 2017).…”
Section: Discussionmentioning
confidence: 99%